2019
DOI: 10.3390/jcm8122107
|View full text |Cite
|
Sign up to set email alerts
|

13-gene DNA Methylation Analysis from Oral Brushing: A Promising Non Invasive Tool in the Follow-up of Oral Cancer Patients

Abstract: Background: This study aimed to evaluate the prognostic value of a non-invasive sampling procedure based on 13-gene DNA methylation analysis in the follow-up of patients previously treated for oral squamous cell carcinoma (OSCC). Methods: The study population included 49 consecutive patients treated for OSCC. Oral brushing sample collection was performed at two different times: before any cancer treatment in the tumor mass and during patient follow-up almost 6 months after OSCC treatment, within the regenerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 46 publications
(76 reference statements)
2
17
0
Order By: Relevance
“…Indeed, it was widely demonstrated that epigenetic modifications represent early events of neoplastic transformation. In this context, the analysis of DNA methylation and miRNAs expression has been proposed for the early diagnosis of different tumors [52][53][54][55]. In line with the results achieved in this study, other studies demonstrated the diagnostic potential of both hsa-miR-133a-3p and hsa-miR-375-3p in different tumors, including gastric cancer, prostate cancer, hepatocellular carcinoma, colorectal cancer, etc., demonstrating the involvement of these miRNAs in cancer development, including that of oral cancer [56][57][58][59][60].…”
Section: Discussionsupporting
confidence: 85%
“…Indeed, it was widely demonstrated that epigenetic modifications represent early events of neoplastic transformation. In this context, the analysis of DNA methylation and miRNAs expression has been proposed for the early diagnosis of different tumors [52][53][54][55]. In line with the results achieved in this study, other studies demonstrated the diagnostic potential of both hsa-miR-133a-3p and hsa-miR-375-3p in different tumors, including gastric cancer, prostate cancer, hepatocellular carcinoma, colorectal cancer, etc., demonstrating the involvement of these miRNAs in cancer development, including that of oral cancer [56][57][58][59][60].…”
Section: Discussionsupporting
confidence: 85%
“…In total, 96.6% ( n = 28) of OSCC and 100% ( n = 6) of high‐grade squamous intraepithelial lesion (HGSIL) specimens exceeded the threshold value, whereas none of the healthy donor samples ( n = 65) exceeded the threshold 13 . The clinical relevance of the method in oral oncology has been confirmed in patients surgically treated for OSCC; the 13‐gene DNA methylation analysis of samples taken from the regenerative area after OSCC resection could identify patients at risk of recurrence during follow‐up 14 …”
Section: Introductionmentioning
confidence: 97%
“…Oral brushing sample collection was performed in the population study as previously described [ 18 , 19 ]; in brief, a cytobrush (manufactured by N.H.M.P. Co., Ltd. PRC EC REP: Shanghai International trading corporation, Hamburg, Germany) was used to collect exfoliated cells from oral mucosa.…”
Section: Methodsmentioning
confidence: 99%
“…DNA methylation analysis was evaluated as previously described [ 18 , 19 ]. In brief, DNA from exfoliating brush specimens was purified using the MasterPure™ Complete DNA Purification Kit (Lucigen, Middleton, WI, USA, cod.…”
Section: Methodsmentioning
confidence: 99%